Semaphorin 3A inhibits allergic inflammation by regulating immune responses in a mouse model of allergic rhinitis. Issue 5 (31st December 2018) - Xiang, Rong; Xu, Yu; Zhang, Wei; Kong, Yong‐Gang; Tan, Lu; Chen, Shi‐Ming; Deng, Yu‐Qin; Tao, Ze‐Zhang
Abstract : Background: It has been reported that semaphorin 3A (sema3A) could improve allergic symptoms in allergic rhinitis (AR) mice. However, the immunomodulatory roles of sema3A in AR remain unclear. This study was performed to determine the immunoregulatory effects of sema3A on airway inflammation in an AR mice model. Methods: First, sema3A expression was measured in the serum of AR patients and also in a mice model. Then, nasal symptoms, ovalbumin (OVA)‐specific immunoglobulin E (IgE) production, cytokine levels, and histologic structure were analyzed in OVA‐sensitized mice, sema3A mice, mice given saline, and controls. The percentages of CD4 + IL‐4 + IFN‐γ ‐ Th2 cells, CD4 + IFN‐γ + IL‐4 ‐ Th1 cells, CD4 + IL‐17 + Th17 cells, and CD4 + CD25 + Foxp3 + Treg cells in the spleen were also analyzed. Results: Serum sema3A levels in both AR patients and OVA‐sensitized mice decreased significantly compared with controls. The intranasal administration of sema3A reduced allergic symptom scores, eosinophil infiltration, and OVA‐specific IgE production in OVA‐sensitized mice. In addition, levels of IL‐4 and IL‐17 as well as percentages of CD4 + IL‐17 + Th17 cells were suppressed by sema3A administration. Levels of IFN‐γ and IL‐10 and ratios of CD4 + IFN‐γ + IL‐4 ‐ Th1/CD4 + IL‐4 + IFN‐γ ‐ Th2 cells, as well as percentages of CD4 + CD25 + Foxp3 + Treg cells, were increased by administration of sema3A. Conclusion: Our results demonstrate that sema3A suppressed allergic inflammation in AR via inhibition of Th2/Th17 responses and enhancement of Th1/Treg responses.